2008
DOI: 10.1037/0097-7403.34.1.155
|View full text |Cite
|
Sign up to set email alerts
|

How the associative strengths of stimuli combine in compound: Summation and overshadowing.

Abstract: When two conditioned stimuli (CSs) are presented in compound, the response is typically stronger than to the individual CSs, implying that their associative strengths combine. However, to identify exactly how associative strengths combine requires an accurate description of the relationship between associative strength and responding. The authors have used the delta rule (Rescorla & Wagner, 1972) to constrain the predicted growth of associative strength (V) to identify the relationship between V and responding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
44
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 27 publications
7
44
2
3
Order By: Relevance
“…Most of these failures have occurred in autoshaping experiments with pigeons (e.g., Aydin & Pearce, 1995, 1997Rescorla & Coldwell, 1995). Nonetheless, both successes and failures to observe summation have been reported in other paradigms, such as the conditioned nictitating membrane response in rabbits (Kehoe, Horne, Horne, & Macrae, 1994) and the conditioned magazine approach with rats (Pearce, George, & Aydin, 2002;Rescorla, 1997;Thein, Westbrook, & Harris, 2008). Such mixed evidence is troubling for any model that assumes that most of the associative strength of each individual CS generalizes to the compound.…”
Section: Summationmentioning
confidence: 86%
“…Most of these failures have occurred in autoshaping experiments with pigeons (e.g., Aydin & Pearce, 1995, 1997Rescorla & Coldwell, 1995). Nonetheless, both successes and failures to observe summation have been reported in other paradigms, such as the conditioned nictitating membrane response in rabbits (Kehoe, Horne, Horne, & Macrae, 1994) and the conditioned magazine approach with rats (Pearce, George, & Aydin, 2002;Rescorla, 1997;Thein, Westbrook, & Harris, 2008). Such mixed evidence is troubling for any model that assumes that most of the associative strength of each individual CS generalizes to the compound.…”
Section: Summationmentioning
confidence: 86%
“…This paradigm measures explicit goal-tracking behavior (entries into the food magazine), which should represent a relatively unambiguous index of learned anticipation of the US. We have recently shown that groupaveraged acquisition functions in this paradigm conform very closely to a simple exponential function (Thein, Westbrook, & Harris, 2008), though as noted above, this could be consistent with either an incremental learning process or arise as an artifact from averaging over many individual step-functions. In both experiments presented here, rats were trained with discrete CSs that were followed by delivery of a food pellet.…”
Section: Ifmentioning
confidence: 99%
“…There are numerous experiments showing that responding to a compound is greater than responding to the individual CSs that make up the compound (e.g., Kehoe, 1982;Kehoe, 1986;Rescorla, 1997;Thein, Westbrook, & Harris, 2008), consistent with the principle of summation.…”
mentioning
confidence: 99%